A novel measure of compulsive food restriction in anorexia nervosa: Validation of the Self-Starvation Scale (SS). (April 2015) - Godier, Lauren R.; Park, Rebecca J.
Abstract: The characteristic relentless self-starvation behaviour seen in Anorexia Nervosa (AN) has been described as evidence of compulsivity, with increasing suggestion of transdiagnostic parallels with addictive behaviour. There is a paucity of standardised self-report measures of compulsive behaviour in eating disorders (EDs). Measures that index the concept of compulsive self-starvation in AN are needed to explore the suggested parallels with addictions. With this aim a novel measure of self-starvation was developed (the Self-Starvation Scale, SS). 126 healthy participants, and 78 individuals with experience of AN, completed the new measure along with existing measures of eating disorder symptoms, anxiety and depression. Initial validation in the healthy sample indicated good reliability and construct validity, and incremental validity in predicting eating disorder symptoms. The psychometric properties of the SS scale were replicated in the AN sample. The ability of this scale to predict ED symptoms was particularly strong in individuals currently suffering from AN. These results suggest the SS may be a useful index of compulsive food restriction in AN. The concept of 'starvation dependence' in those with eating disorders, as a parallel with addiction, may be of clinical and theoretical importance. Highlights: The Self-Starvation Scale (SS) was developed to index compulsive food restriction behaviour in eating disorders. The SS demonstrated good construct validity and reliability, and predicted eating disorder symptoms in a community sample. The psychometric properties of the SS were replicated in individuals with experience of Anorexia Nervosa. These results suggest the SS may be a useful index of compulsive food restriction in Anorexia Nervosa.